2019
DOI: 10.3389/fphar.2019.00059
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Role of GRK2 in the TLR Signaling-Mediated iNOS Induction Pathway in Microglial Cells

Abstract: G protein-coupled receptor kinase 2 (GRK2) is a ubiquitous member of the GRK family that restrains cellular activation by G protein-coupled receptor (GPCR) phosphorylation leading to receptor desensitization and internalization, but has been identified to regulate a variety of signaling molecules, among which may be associated with inflammation. In this study, we attempted to establish the regulatory role of GRK2 in the Toll-like receptor (TLR) signaling pathway for inducible nitric oxide synthase (iNOS) expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…GRK2 has been identified to regulate a variety of pro‐inflammatory secretions. The high expression of nitric oxide synthase (iNOS) in microglial cells is caused by GRK2, which significantly enhances the phosphorylation levels of STAT1 and STAT3 through regulating the toll like receptor ( 53 ). The upregulation of iNOS could promote the secretion of inflammatory cytokines and development of many fibrous diseases ( 54 ).…”
Section: Relationship Between Grk2 and Fibrosis-associated Pathwaysmentioning
confidence: 99%
“…GRK2 has been identified to regulate a variety of pro‐inflammatory secretions. The high expression of nitric oxide synthase (iNOS) in microglial cells is caused by GRK2, which significantly enhances the phosphorylation levels of STAT1 and STAT3 through regulating the toll like receptor ( 53 ). The upregulation of iNOS could promote the secretion of inflammatory cytokines and development of many fibrous diseases ( 54 ).…”
Section: Relationship Between Grk2 and Fibrosis-associated Pathwaysmentioning
confidence: 99%
“…Palikhe et al. have shown that GPCR kinase‐2 regulates transcription of iNOS in microglial cells by regulating activation of IRF‐1 and the STAT pathway 36 . Our results suggest that GPCRs including G2A that sense circulating lipids such as LPC might play a vital role in amplifying TLR‐mediated inflammatory and innate immune responses.…”
Section: Resultsmentioning
confidence: 56%
“…34,35 Palikhe et al have shown that GPCR kinase-2 regulates transcription of iNOS in microglial cells by regulating activation of IRF-1 and the STAT pathway. 36 Our results suggest that GPCRs including G2A that sense circulating lipids such as LPC might play a vital role in amplifying TLR-mediated inflammatory and innate immune responses. These findings have significant implications not only for inflammatory responses produced during infections but these are also relevant to chronic inflammation as the presence of circulating TLR agonists such as LPS has been suggested to be a critical factor in the induction of inflammatory response in several experimental models of chronic inflammatory disorders.…”
Section: Serum/lpc Produce Enhancement Of Tlr-responses Through Gpcr-mentioning
confidence: 71%
“…The current study highlights the important role of GRK2 in mediating colitis and suggests that GRK2 might be a potential drug target for IBD. A previous study demonstrated that GRK2 played a direct role in regulating TLR4‐mediated inflammatory signaling in microglia cells 56 . TLR4 is the main pattern recognition receptor expressed on the cell surface of macrophages 57 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that GRK2 played a direct role in regulating TLR4-mediated inflammatory signaling in microglia cells. 56 TLR4 is the main pattern recognition receptor expressed on the cell surface of macrophages. 57 Membrane localization of GRK2 increases in inflammatory macrophages, and GRK2 has been shown to promote the polarization of macrophage phenotypes to antiinflammatory macrophages.…”
Section: Discussionmentioning
confidence: 99%